(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
لقد أظهرت طرائق تجميع النماذج في مجالي التصنيف (Classification) والتقهقر أو التتالي (Regression) تفوقها على الطرائق الأخرى نظرياً وعملياً. والـBoosting هي إحدى هذه الطرائق التي أثبتت فعاليتها و مقدرتها على تحسين نتائج أي خوارزمية تعليمية. لقد قمنا في هذا البحث باستخدام الخوارزمية Boosting مع الشبكات العصبونية الصنعية التكرارية وذلك في مجال تنبؤ السلاسل الزمنية بخطوة زمنية واحدة بالاعتماد على مجموعة اختبار كل سلسلة زمنية. هذه السلاسل معروفة بتطبيقاتها الواسعة في مجالات عديدة. ثم قورنت النتائج التي تم الحصول عليها باستخدام الخوارزمية المطروحة بأفضل النتائج التي تم الحصول عليها باستخدام خوارزميات أخرى. وأظهرت هذه النتائج مقدرة الشبكات العصبونية الصنعية على تنبؤ السلاسل الزمنية و أن تجميع نتائج عدة شبكات باستخدام الـBoosting يعطي نتائج أكثر استقراراً من النتائج التي نحصل عليها باستخدام شبكة عصبونية واحدة. Ensemble methods used for classification and regression have shown that they are superior than other methods, theoretically and empirically. Boosting is one of these methods which is a powerful tool for improving the performance of any learning algorithm. In this research, we have used Boosting algorithm with Recurrent Neural Networks in Regression context to predict time series on single-step ahead depending on each test set of time series. These series are known by its wide applications in many fields. Then, the final results by using Boosting algorithm have been compared with the best obtained results by using other algorithms. These results have also shown the ability of Artificial Neural Networks (ANNs) in predicting time series. Also combination results of many ANNs by using Boosting algorithm give more stability than results that obtained by using single neural network.